A Crosswalk Analysis Between Magnet® Standards and Clinical Nurse Specialist Practice Competencies. Issue 7 (July 2022) - Fulton, Janet S.; Gilbert, Jason H.; Rader, Tiffany; Keen, Alyson; Shay, Amy C.; Moody, Rachel; Walker, Jane
Abstract : OBJECTIVE: The purpose of this study was to determine the alignment between the American Nurses Credentialing Center's Magnet Recognition Program ® standards and clinical nurse specialist (CNS) practice competencies. BACKGROUND: Despite documentation of CNS contributions to achieving and sustaining Magnet Recognition ®, there is a lack of evidence clearly aligning Magnet ® standards and CNS practice competencies. METHODS: Using a crosswalk method, an expert panel of CNSs and chief nursing executives analyzed alignment of the 50 Magnet standards with the 44 National Association of Clinical Nurse Specialists core practice competencies. RESULTS: CNS practice competencies are aligned closely with Magnet standards: 86% of the 50 Magnet standards aligned with at least 1 CNS competency and 81.8% of CNS competencies aligned with at least 1 Magnet ® standard. CONCLUSIONS: The alignment between Magnet standards and CNS competencies supports evidence of CNS contributions to organizational achievement of Magnet Recognition and will assist nurse executives in identifying a full scope of opportunities for CNSs to contribute to nursing excellence.